IMPLEMENTASI PENGEMBANGAN KEMASAN UMKM BERBASIS ENGINEERING GUNA MENINGKATKAN DAYA SAING PRODUK: IMPLEMENTASI PENGEMBANGAN KEMASAN UMKM BERBASIS ENGINEERING GUNA MENINGKATKAN DAYA SAING PRODUK - imam, saeful; Purnama Sari, Novi; Muryeti, Muryeti; Silvia, Deli; Sinur, Valeri Vela; Prastiwinarti, Wiwi; Yamin, Iqbal; Zulkarnain, Zulkarnain (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
Micro, small and medium-sized enterprises (MSMEs) play an important role in the Indonesian economy, especially in creating jobs and driving local economic growth. However, many MSMEs, including peyek producers, face difficulties to become more competitive in an increasingly competitive market. One of them is Peyek Bude Asih MSMEs that produce delicious and savory products and are favored by many customers, but still use simple and unrepresentative packaging. Non-optimal packaging is an obstacle for MSMEs to market their products to more people and increase their selling value. Based on this Community Service Activity includes exposure to packaging developments and trends, handover of equipment and packaging to Bude Asih MSMEs, as well as clinical coaching sessions to ten MSMEs. In packaging development, the method used in this research is the Kansei engineering method which can translate consumer expectations of products into packaging design concepts. The results of the questionnaire are processed into PCA input data using Kansei Engineering-based software, the methods used include collecting packaging samples, identifying kansei words, processing data with R software, and determining the selected packaging design concept.